(untitled) (Research, Society and Development, 2023)
Post-acute COVID-19 syndrome (also known as long COVID) refers to the persistence of COVID-19 symptoms for at least four weeks following the acute phase of the disease caused by SARS-CoV-2 infection. This study aims to provide a narrative review of the musculoskeletal manifestations of long COVID-19. While prevalence rates varied among studies, chronic fatigue, myalgia, arthralgia, and arthritis were consistently reported as the most common manifestations. Notably, a positive correlation was observed between the length of hospital stay and the likelihood of experiencing long COVID-19 symptoms. Moreover, women were found to be more susceptible to this condition than men.